IMPLEMENTASI BAHAN AJAR KALULUS LANJUT BERBASIS INKURI - Nurul Farida; Rina Agustina (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
In advanced calculus learning is needed teaching materials that can help students understand the concept. One of the teaching materials that can be used is by applying teaching materials that contains the problem of understanding the concept of advanced calculus. This instructional material can be arranged with inquiry-based. The research design used is Pre-Experimental Design with One-Group Pretest-Posttest Design type. From result of research, obtained t count equal to 11,8 and t tabel equal to 1,645 mean value of concept comprehension after given instructional materials advanced calculus based on inquiry is significantly better than before using advanced calculus based instructional materials inquiry. Based on the results of data analysis concluded that the instructional materials advanced inquiry-based advanced calculus developed effectively can improve the ability of students' concept of understanding on advanced calculus learning.